Florentia Studi di archeologia: vol. 4 - Vannini, Guido (Strumenti per la didattica e la ricerca, 2019)
Thanks to this fourth volume belonging to a series which well represents the Department of Specialization in Archaeological Heritage of the University of Florence, it has been possible to restore a continuity, albeit with long intervals, which the editorial staff intends to consolidate by involving the entire Department's "community" (while maintaining the importance of the students' 'space'). The essays included in the volume, coming from every diachronic curriculum in the Department (pre-protohistoric, oriental, classical, medieval), bring out some trends, among which are the growth of interest in Islamic archaeology (an unexplained countertrend, nowadays), the full transversality of public archaeology or the confirmed articulation of the themes characterising the classical sector since its foundation. Furthermore, the variety of the students' backgrounds is validated, both as basic training and as an academic matrix, confirming the Department's good response to current needs and expectations.